2010
DOI: 10.1007/s00534-010-0320-2
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic procedures for IgG4-related sclerosing cholangitis

Abstract: Background/purpose IgG4-related sclerosing cholangitis (IgG4-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 52 publications
(111 reference statements)
2
17
0
1
Order By: Relevance
“…Clinically, PSC usually occurs in younger patients and presents with obstructive jaundice more commonly than IgG4-SC. PSC is commonly associated with inflammatory bowel disease, whereas IgG4-SC is associated with autoimmune pancreatitis 3. The measurement of serum IgG4 levels is useful for differentiating between these two disorders; according to previous studies, increased serum IgG4 levels exceeding 135 mg/dL are frequently seen in these patients 4…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, PSC usually occurs in younger patients and presents with obstructive jaundice more commonly than IgG4-SC. PSC is commonly associated with inflammatory bowel disease, whereas IgG4-SC is associated with autoimmune pancreatitis 3. The measurement of serum IgG4 levels is useful for differentiating between these two disorders; according to previous studies, increased serum IgG4 levels exceeding 135 mg/dL are frequently seen in these patients 4…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have stated that combined histological findings and positive immunostaining are not enough to diagnose IgG4-SC [18]. Therefore, other diagnostic tools as serum markers and radiologic studies are essential, not only for IAC diagnosis, but also for ruling out the possibility of cholangiocarcinoma, especially in patients' presenting with hilar cholangiopathy [19]. ERCP had displayed superior results over the less invasive MRCP in recognition of early or single large duct PSC.…”
Section: Discussionmentioning
confidence: 99%
“…It is at present known and accepted that immunoglobulin G4 (IgG4)-associated cholangitis (IAC) is one of several diseases associated with autoimmune pancreatitis (AIP) [1, 2, 3]. However, IAC may occur in 20–90% of cases of AIP whereas a study of the Mayo Clinic recently revealed that 92.5% of patients with IAC suffer from AIP [4, 5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…A possible involvement of Helicobacter pylori in the initiation of the autoimmune process is speculated [7, 8, 9]. Typical results concerning blood values are high IgG4 concentrations, which can be seen as a useful indicator to differentiate between other pancreatic or bile duct diseases [1, 2, 3, 4, 10]. IgG4-related diseases such as AIP and IAC have typical histopathological features in common showing a diffuse infiltration with lymphocytes and IgG4-positive plasma cells [1, 2, 4, 7, 10].…”
Section: Introductionmentioning
confidence: 99%